The contribution of p.v. alabin into the development of education and culture in the vyatka province - Vladimir B. Pomelov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The biographical data and the main stages of the life of the prominent Russian statesman of the 19th century Peter Vladimirovich Alabin (1824-1896) and revealed in the article. He proved brightly in various areas: as a soldier, memoirist, writer, civil servant, publisher, archaeologist, creator of schools, museums and libraries. The focus of the article is given to disclose the contribution of P.V. Alabin into the development of education and culture in the Vyatka province, where he spent 9 years (1857-1866). During these years he had made efforts to radically improve the work of the provincial public library, which had been opened by A.I. Gercen in 1837. Alabin transformed Vyatka antiques warehouse into a full-fledged museum, which celebrated its 150th anniversary in 2016. For the first time in the history of the Vyatka provinceP.V. Alabin organized archaeological surveys, which have brought rich scientific material. He had made a lot of effort to the opening of new schools and their better equipping.